2017
DOI: 10.1093/schbul/sbx102
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Remission in Subjects at Clinical High Risk for Psychosis Using Mismatch Negativity

Abstract: These results suggest that MMN is a putative predictor of prognosis regardless of the transition to psychotic disorder in subjects at CHR. Early prognosis prediction and the provision of appropriate interventions based on the initial CHR status might be aided using MMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 43 publications
2
39
1
Order By: Relevance
“…This study revealed that the MMN could be a significant predictor for remission and symptom improvement, as well as functional outcomes, in patients with schizophrenia. Recent studies showed that MMN was a putative predictor of symptom improvement and remission, regardless of the transition to a psychotic disorder in subjects at high clinical risk [18]. This study proposed that MMN could be associated with remission, not only in subjects at high clinical risk but also in the patients diagnosed with schizophrenia.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This study revealed that the MMN could be a significant predictor for remission and symptom improvement, as well as functional outcomes, in patients with schizophrenia. Recent studies showed that MMN was a putative predictor of symptom improvement and remission, regardless of the transition to a psychotic disorder in subjects at high clinical risk [18]. This study proposed that MMN could be associated with remission, not only in subjects at high clinical risk but also in the patients diagnosed with schizophrenia.…”
Section: Discussionmentioning
confidence: 89%
“…These stimuli were presented through MDR-D777 headphones (Sony, Tokyo, Japan). The peak amplitude and latency of the MMN were determined as the most negative peak between 130 milliseconds and 250 milliseconds of the subtracted waveform using a peak detection method at six electrode sites (Fz, F3, F4, FCz, FC3, and FC4) [18].…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a shorter duration of untreated psychosis is associated with a greater response to antipsychotic treatment in first-episode schizophrenia [ 58 ]. Our results indicated that patients with a higher level of education achieved greater clinical improvement, which was predictable from the improvement in attenuated positive symptoms among individuals at high risk [ 59 ]. However, why different clinical features affect different clinical categories might need to be explored in greater detail in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In a 6-year follow-up study comparing 47 healthy controls and 48 participants with CHR for psychosis, CHR nonremitters had reduced MMN at baseline compared to CHR remitters and healthy controls. The baseline MMN was the only significant predictor of remission [28]. …”
mentioning
confidence: 99%